Graphene oxide enhances the specificity of the polymerase chain reaction by modifying primer-template matching - Yuanyuan Wang (Nature Portfolio, 2017)
Abstract Aiming at improved specificity, nanoparticle assisted polymerase chain reaction (PCR) has been widely studied and shown to improve PCR. However, the reliability and mechanism of this method are still controversial. Here, we demonstrated that 1 μg/mL of graphene oxide (GO) effectively enhances the specificity of the error-prone multi-round PCR. Mismatched primers were designed as interference to produce nonspecific products when the same amounts of matched and mismatched primers were added into semi-multiplex PCR. It was found that GO can enhance specificity by suppressing the amplification of mismatched primers. We monitored the primer-template-polymerase-GO interactions involved in the PCR using a capillary electrophoresis/laser-induced fluorescence polarization (CE-LIFP) assay. The results showed that the addition of GO promoted the formation of a matched primer-template complex, but suppressed the formation of a mismatched primer-template complex during PCR, suggesting that interactions between the primers and GO play an essential role. Furthermore, we successfully amplified the FOXL2 gene from PEGFP-N1 vectors using GO to eliminate the nonspecific products in PCR. Taken together, these results suggest that the GO can be used as an efficient additive for improving the conventional PCR system.